Analysis of the Development of E-Commerce Transactions in the 6 Highest Transaction Countries in Southeast Asia - A'yun, Indanazulfa Qurrota; Anggraini, Lusiana; Asmara, Gea Dwi; Khoirunnisa, Rikha Muftia (Journal of Economics Research and Social Sciences, 2024)
The background of this study is driven by the significant growth of the internet, particularly in the Southeast Asian region, which has led to technological advancements and the emergence of e-commerce. E-commerce has become crucial for meeting consumer needs, highlighting the necessity to further enhance the potential of economic digitalization through e-commerce. This study aims to examine the impact of e-commerce development factors on the growth of e-commerce transaction values in six Southeast Asian countries. It utilizes secondary data sourced from the official e-Conomy SEA website and DataReportal. The research employs panel data regression analysis using the Random Effects Model (REM) approach. The findings indicate that increases in population, number of social media users, and mobile phone users significantly contribute to the growth of e-commerce transaction values, urging platform developers and policymakers to enhance digital infrastructure and marketing strategies to maximize the digital economy potential in Southeast Asia.